LEVEL OF DEPENDENCE OF STROKE PATIENTS BASED ON THE BARTHEL INDEX SCORES IN ACTIVITY DAILY LIVING - sri sudarsih; Windu Santoso (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Stroke is a major cause of long-term disability resulting in the inability to perform daily activities (ADL). Various daily activity assessment scales have been used for stroke patients including the Barthel Index. This study aims to determine the level of dependence of stroke patients based on the Barthel index score in daily living activities. This research is a descriptive study, where the research sample is stroke patients in the working area of ​​the Kedundung Public Health Center, Mojokerto City, totaling 60 people using a consecutive sampling technique. Data collection using the Barthel index instrument to assess the ability of ADL. Data were analyzed using frequency distribution. The results showed that most of the respondents had mild dependence, namely 78.4% and 13.3% of respondents were independent in ADL abilities. The severity of the respondent's dependence on performing ADL ability also depends on the severity of stroke symptoms. Patients with mild stroke may also experience ADL dependence in daily life. Appropriate and effective evaluation of ADL in stroke patients can be used as a basis for decision-making in treatment, rehabilitation, and nursing actions.